1998
DOI: 10.1182/blood.v92.8.2759.420k29_2759_2765
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Induces the Antiapoptotic Molecules, A1 and A20, in Microvascular Endothelial Cells

Abstract: The effect of lipopolysaccharide (LPS) on endothelial cells is a key component of the inflammatory response seen in Gram-negative sepsis. LPS does not cause death of cultured human endothelial cells. However, when the expression of new proteins is inhibited by cycloheximide, microvascular endothelial cells in culture undergo apoptosis. This finding suggests that LPS induces apoptotic and antiapoptotic pathways, with the antiapoptotic response being dependent on the synthesis of new proteins. Concurrent activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 56 publications
0
27
0
1
Order By: Relevance
“…Ang1 directly promotes endothelial anti‐apoptotic and anti‐inflammatory effects via the A20‐binding inhibitor of NF‐κB activation (ABIN)‐2 . A20 inhibits TNF‐α and LPS‐mediated EC apoptosis and reduces NF‐κB expression, and ABIN‐2 mediates these effects via Tie2 in an Ang1‐dependent fashion . Furthermore, we observed decreased mRNA expression and immunoreactivity of danger signals HAS1 and TLR4 and dendritic cell activation markers CD80 and CD83 in the COMP‐Ang1–treated allografts.…”
Section: Discussionmentioning
confidence: 75%
“…Ang1 directly promotes endothelial anti‐apoptotic and anti‐inflammatory effects via the A20‐binding inhibitor of NF‐κB activation (ABIN)‐2 . A20 inhibits TNF‐α and LPS‐mediated EC apoptosis and reduces NF‐κB expression, and ABIN‐2 mediates these effects via Tie2 in an Ang1‐dependent fashion . Furthermore, we observed decreased mRNA expression and immunoreactivity of danger signals HAS1 and TLR4 and dendritic cell activation markers CD80 and CD83 in the COMP‐Ang1–treated allografts.…”
Section: Discussionmentioning
confidence: 75%
“…Various methods were employed to measure endothelial injury in these studies. For example, Hu et al examined cell viability by MTT assay [30] and Bannerman et al examined caspase activities [24]. In the present study, we systematically evaluated endothelial injury with the MTS viability assay, LDH release (cytotoxicity) and caspase-3/7 activity both intracellularly and in culture supernatants in the presence and absence of a protein synthesis inhibitor, CHX.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…ACCEPTED MANUSCRIPT [28][29], most studies using human endothelial cells showed that these cells require protein synthesis inhibitors such as CHX for the induction of apoptosis in response to LPS [24,30]. Various methods were employed to measure endothelial injury in these studies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[61][62][63][64][65] Induced expression of FLICE-like inhibitory protein (FLIP) and the antiapoptotic proteins A1 and A20 have a role in protecting endothelial cells from LPS-induced apoptosis as well as in creating a suppressive effect on LPS-induced NFkB activation. 66,67 For an overview on the more detailed molecular interactions of these signaling pathways, the reader is referred to two excellent reviews. 61,65 The functional consequences of LPS-mediated endothelial cell activation are widespread and include engagement in leukocyte recruitment, expression of procoagulant activity, and endothelial sprouting.…”
Section: Interleukin-1 Effects On Endothelial Cellsmentioning
confidence: 99%